EFFECT OF REPLACING COMMERCIAL RATION WITH CRICKET MEAL (Gryllus mitratus Burm) ON BROILER PERFORMANCE - I. E., Gabriel,; Astawa, I P. A.; Puspani, E. (Jurnal Peternakan Tropika, 2024)
Broiler is one of the sources of animal protein with a relatively affordable price and easily obtained is broiler meat. This study aims to determine the effect of replacing cricket flour ( Gryllus mitratus Burm ) in commercial rations on broiler performance. This research will be conducted in teaching farm Sesetan, Faculty of Animal Husbandry Udayana which lasted for 24 days. The research design used is a completely randomized design (CRD) consisting of 4 treatments and four replicates, each replicate containing four broilers. The treatments given were commercial rations without replacement of cricket flour (P0/control); 2% commercial rations replaced with 2% cricket flour (P1); 4% commercial rations replaced with 4% cricket flour (P2); 6% commercial rations replaced with 6% cricket flour (P3). The observed variables were initial body weight, body weight gain, final body weight, ration consumption, and FCR (Feed Conversion Ratio). The results showed that in the treatment of 2%, 4%, and 6% showed a real effect (P <0.05) can increase the final body weight, but in the variable initial body weight, ration consumption and FCR in the treatment of 2%, 4%, and 6% did not show a real effect (P>0.05). The results of the study can be concluded that replacing commercial rations with cricket flour at the 2% level can increase final body weight. While at the level of 4% and 6% can increase the final body weight and body weight gain.